Remote monitoring and controlling of lights using IoT / Nurul Najihah Yusra Zolkarnain, Nurzaid Muhd Zain and Mahfudzah Othman - Zolkarnain, Nurul Najihah Yusra; Muhd Zain, Nurzaid; Othman, Mahfudzah (College of Computing, Informatics and Media, UiTM Perlis, 2023)
As technology advances and improves to benefit the environment, daily living has become significantly easier and more convenient. Our lives are becoming increasingly intertwined with the Internet of Things (IoT) as a result of the technological advancement. IoT is a network of physical objects embedded with sensors, software, and other technologies that connect to and exchange data with other devices and systems via the internet. Since humans are prone to forgetting things, it's tough to steer clear of this predicament. As a result, electricity is wasted and the problem of forgetting to turn off the lights is not addressed. The rising cost of electricity is a result of this predicament. Smart lighting is used to conserve energy. This study discusses about developing a prototype of smart lighting system using IoT. The system is supported by Blynk application and Arduino. A smart phone app will be used to monitor and manage all of a house or office's lights remotely. Arduino will be the electronic prototyping platform utilized in this project. Blynk servers will be used to monitor and control remote devices.